Radiation-induced processes and defects in purified CsI crystals - Garapyn, I.; Pavlyk, B.; Tsybulyak, B. (Functional Materials, 2007)
Defect formation processes under γ-ray irradiation (up to doses of 10⁴-5*10⁶ Gy) in purified Csl crystals have been studied using the electric conductivity measurements, optical absorption spectra and the thermostimulated depolarization currents. The processes of accumulation and destruction of defects have been found to run in different manners depending on the γ-irradiation dose. Starting from a dose of 10⁵ Gy, the γ-irradiation affects appreciably the defect structure of the purified cesium iodide crystals.